Rasāʾil-i Ḥazīn-i Lāhijī - Ṭālib, Muḥammad ʿAlī b. Abī, (Miras Maktoob, ISBN: 9789004365452., 2019)
Born into a wealthy intellectual family in Isfahan, Muḥammad ʿAlī b. Abī Ṭālib, better known as Ḥazīn Lāhijī (d. 1180/1766), was a particularly gifted child. Greatly stimulated by his father, he received a varied education: from literature and the traditional Islamic sciences to mysticism, logic, philosophy and more. Until the siege of Isfahan by the Afghans in 1135/1722, Ḥazīn lived mostly in that city. He then fled the capital, leading a wandering existence in Persia, Arabia and Iraq. Ten years later and seeing no future for Persia, he left the country for good to settle in India, dying in Benares, aged 74. Ḥazīn is mostly famous as a poet and intellectual who left his imprint on India's Persian-speaking, ruling élites. His attractive prose-pieces on a wide variety of subjects, from Qurʾān interpretation and knowledge of the soul to pearl-diving and the lifting of weights, are much less known. The present volume aims to fill this gap.